GOVERNMENT POLICY IN MITIGATING THE ECONOMIC CRISIS DUE TO THE IMPACT OF THE COVID-19 OUTBREAK - Muhammad Ishar Helmi, Rezky Panji Perdana Martua Hasibuan, Nur Rohim Yunus (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The COVID-19 pandemic outbreak has spread significantly throughout the world. The threat from various sectors also haunted affected countries, including Indonesia. In addition to having an impact on health emergencies, the presence of this virus also has implications for several financial sectors that have caused the economic system to become unstable. With the worst possibility, an economic crisis could occur due to recession as a result of the outbreak of the Covid-19 pandemic. Based on these conditions requires the state's role to be responsive and active. Various policies of each country were also presented to prevent the spread and to guarantee protection and maintain the stability of the country. In the concept of constitution, the role of the state through the government is the initial foundation and the frontline to address a situation which will be supported by various sector lines. This research will comprehensively examine the situation of the Covid-19 pandemic outbreak in Indonesia, and the role of the government in handling pandemics, as well as efforts to mitigate the country's economic crisis. This research uses normative research using a statutory approach and legal materials obtained through library research as a source of reference supported by data from state and non-state institutions. The results of this study explain the role and effort of the state in handling pandemics as a form of risk mitigation against economic crises due to pandemic outbreaks. This is to manifest the purpose of the state's presence, namely to protect the entire Indonesian nation.